(untitled) (Indo-MathEdu Intellectuals Journal, 2023)
This study aims to improve the ability to write procedural texts of students of class IX B SMP Negeri 1 Alasa Talumuzoi by using Picture and Picture Learning Model. The type of research is Classroom Action Research with the stages of planning, action, observation, and reflection. The research data is in the form of qualitative and quantitative data. The research sample was students of class IX B SMP Negeri 1 Alasa Talumuzoi. The results showed that in cycle I, the average score of students was 68.93 with the qualifications of excellent 7%, good 27%, sufficient 30%, and less 37%. In cycle II, the average score of students was 83.67 with excellent qualifications 33.33%, good 50%, sufficient 16.67%. Based on the results of the study, the application of Picture and Picture Learning Model can improve the ability to write procedure text of students of class IX B SMP Negeri 1 Alasa Talumuzoi.